2010
DOI: 10.1097/qad.0b013e32833298be
|View full text |Cite
|
Sign up to set email alerts
|

Antiretroviral therapy in antenatal care to increase treatment initiation in HIV-infected pregnant women: a stepped-wedge evaluation

Abstract: An integrated ART in ANC strategy doubled the proportion of treatment-eligible women initiating ART while pregnant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
117
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(121 citation statements)
references
References 18 publications
2
117
1
1
Order By: Relevance
“…Four studies met the inclusion criteria (Table 1); three of them reported on ART enrolment [30][31][32] and all four reported on ART coverage. [29][30][31][32] All studies were conducted in self-identified ANC clinics; none was conducted in a selfidentified MCH clinic. One study was a prospective cohort study 30 and the other three were retrospective cohort studies.…”
Section: Search Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Four studies met the inclusion criteria (Table 1); three of them reported on ART enrolment [30][31][32] and all four reported on ART coverage. [29][30][31][32] All studies were conducted in self-identified ANC clinics; none was conducted in a selfidentified MCH clinic. One study was a prospective cohort study 30 and the other three were retrospective cohort studies.…”
Section: Search Resultsmentioning
confidence: 99%
“…[29][30][31][32] All studies were conducted in self-identified ANC clinics; none was conducted in a selfidentified MCH clinic. One study was a prospective cohort study 30 and the other three were retrospective cohort studies. 29,31,32 Moreover, no studies meeting eligibility criteria were found by contacting experts or by searching the Cochrane Central Register of Controlled Trials, the International Standard Randomized Controlled Trial Number Register, or the reference lists of studies meeting inclusion criteria.…”
Section: Search Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This rate was comparable with those reported globally. [18][19][20][21][22][23] The sociodemographic, HIV disease (WHO clinical stage or CD4 cell count), and gestational age at HIV diagnosis were not associated with ART initiation in our study. Data on the importance of these factors in ART acceptance have been questionable, with conflicting results between studies.…”
Section: Discussionmentioning
confidence: 78%
“…A systematic review found that ART integration into MNCH facilities significantly improves ART uptake (risk ratio 1.37, 95% confidence interval (CI): 1.05, 1.79) . However, only one study has evaluated the effect of facility-based integration of MNCH and PMTCT on retention in care (Killam et al 2010) and none has evaluated ART adherence.…”
Section: Theory Of Changementioning
confidence: 99%